Analysis and Modeling of an Actuation System To Be Used in Light-Weight Collaborative Robots - Yılmaz, Mert; Dede, Mehmet İsmet Can (Izmir Institute of Technology, 2019)
Collaborative robots are a relatively new concept in robotics and industrial automation. Traditional industrial robots are relatively expensive, heavy, and dangerous devices for humans since they are enclosed in working cells with fences. Nowadays, in small and medium enterprises (SMEs), instead of traditional robots lightweight and versatile robots are required which can work alongside human co-workers. In such applications, human safety is a critical factor. ISO has produced new standards for these robots to regulate their collaborative work with human co-workers and named these robots as collaborative robots. The subject of the thesis is related to the actuation systems of light-weight collaborative robots. For these robots, a variety of actuation systems are designed in recent years which are usually modular and compact actuation systems. The main aim of the thesis is to analyze and model of a commonly used actuation system in collaborative robots and to verify its model.

İşbirlikçi robotlar robotikte ve endüstriyel otomasyonda nispeten yeni bir konsepttir. Geleneksel endüstriyel robotlar nispeten pahalı, ağır ve çitlerle çevrelenmiş çalışma hücreleri içinde olan, insanlar için tehlikeli cihazlardır. Günümüzde, küçük ve orta ölçekli işletmelerde (KOBİ’ler), geleneksel robotlar yerine, insan iş arkadaşlarıyla birlikte çalışabilecek hafif ve çok yönlü robotlara ihtiyaç duyulmaktadır. Bu tür uygulamalarda insan güvenliği kritik bir faktördür. ISO, bu robotların insan meslektaşlarıyla ortak çalışmalarını düzenlemek için yeni standartlar üretmiş ve bu robotları işbirlikçi robotlar olarak adlandırmıştır. Tezin konusu hafif işbirkçi robotların eyleyici sistemleriyle ilgilidir. Bu robotlar için, son yıllarda genellikle modüler ve kompakt olmak üzere çeşitli eyleyici sistemler tasarlanmıştır. Tezin temel amacı işbirlikçi robotlarda genel olarak kullanılan eyleyici sistemi analiz etmek, modellemek ve modelini doğrulamaktır.
Hafif İşbirlikçi Robotlarda Kullanılacak Eyleyici Sistemin Analizi ve Modellenmesi
Thesis (Master)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2018
Includes bibliographical references (leaves: 82-86)
Text in English; Abstract: Turkish and English
Keywords: Collaborative robots; Industrial robots; Actuation systems